Encyclopedia britannica. Micropedia VOL. 10. / William Benton - Benton, William (Estados Unidos de América: Encyclopedia britannica, Inc, 1977)
Cross refences appear often, identified by see also, or as related entries, and always refer to other entries in the ready reference and index in alphabetical order volumes 1-x; entries are alphabetized as if the were one word, up to the comma, regardless of the number of words in the title, thus; directions, or index references, are given to the page in the macropedia (vol 1 19) on which a subject or aspect of a subject may be found in the longer articles; volume and page numbers immediately follow the title of an entry always refer to a comprehensive articles in volumes 1through19, all other volume and page references follow the text and cit sections of the longer (macropadia9) articles.
Ilustración, mapa, tabla
Col. Ref
Keywords: 1. ENCICLOPEDIA 2. ENCYCLOPEDIA BRITANNICA-MICROPEDIA VOL. 10. 3. REFERENCIA